1976
DOI: 10.1104/pp.58.2.143
|View full text |Cite
|
Sign up to set email alerts
|

Variables Affecting the CO2 Compensation Point

Abstract: Some factors influencing dark respiration, photorespiration, and photosynthesis were examined for their effect on the CO2 compensation point (70 ,Ill) of detached soybean (Glycine max) leaf discs. A higher compensation point in young leaves decreased to the constant value after leaf expansion and maturation, but increased again during senescence.The compensation point was 40 to 50% higher in plants grown in the summer than in the winter. The compensation point and dark respiration increased with temperatures a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
0
2

Year Published

1978
1978
2009
2009

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(13 citation statements)
references
References 17 publications
4
7
0
2
Order By: Relevance
“…The same results occurred with C. fracta in a similar study (Cheney and Hough 1983); others have reported that HMS can act as a general inhibitor to photosynthesis (Smith et al 1976) and to other metabolic processes (Lian and Sin 1974).…”
Section: Discussionsupporting
confidence: 80%
“…The same results occurred with C. fracta in a similar study (Cheney and Hough 1983); others have reported that HMS can act as a general inhibitor to photosynthesis (Smith et al 1976) and to other metabolic processes (Lian and Sin 1974).…”
Section: Discussionsupporting
confidence: 80%
“…We compared the CO 2 compensation point (G) of wild-type and transgenic plants (Fig. 5) because it has been shown previously that senescence or water stress can increase G with a concomitant increase in photorespiration (Smith et al, 1976). No significant differences were observed between wildtype and transgenic plants grown under optimal watering conditions, but differences were seen after 40 d of growth under water-limiting conditions (Fig.…”
Section: Ck-dependent Photorespirationmentioning
confidence: 99%
“…It was noted earlier in Fig. Smith et al (1976) found that the C02 compensation point fell when plants were exposed to solutions containing organic solvents. It is unlikely that the higher ci levels observed after the first leachate treatment were caused by increased plant respiration given their condition of acute stress.…”
Section: Discussionmentioning
confidence: 63%